Analysis of Entrepreneurial Skills in the Commercialization of Pineapple Fiber Woven Textile - Jumie SL Mokoginta; Elva Pobela; Sarah Annamira Lasabuda; Meriyati Pobela (Journal of Economics, Business, and Accountancy Ventura, 2026)
This study analyzes entrepreneurial skills in the commercialization of pineapple fiber woven fabrics among pineapple fiber woven fabric artisans at the Morobayat LKS (Social Welfare Institution) in the West Passi District, Bolaang Mongondow Regency, and maps the internal and external factors that influence them. The method used was a qualitative descriptive method, namely data collected through interviews, observations, documentation, and SWOT analysis supported by the IFE and EFE matrices. The findings indicate that skills such as creativity and innovation, business management, communication skills, market analysis, and environmental awareness, and networking and collaboration are very important in transforming pineapple fiber into valuable woven fabrics, which contribute to the economic independence of the community. The IFE score (0.8) indicates strong internal factors, especially abundant raw materials and distinctive local motifs. The EFE score (1.0) indicates more dominant external opportunities, including the trend towards environmentally friendly products, government support, and tourism potential. The SWOT analysis places the industry in quadrant I (aggressive strategy), recommending increased innovation, digital marketing, and external collaboration. In conclusion, entrepreneurial skills combined with favorable internal and external factors are crucial for the successful commercialization of pineapple fiber woven fabric as a competitive local product.